The effect of the desensitization and REM techniqueconference - Hussein Faleh Hussein; Adnan Abdul Rahman (Zanco Journal of Humanity Sciences)
That mental illnesses are many and numerous, and all of these diseases have their causes and treatment, and among these diseases is the panic disease, as many studies have shown that about (10-20%) of people have experienced panic, which is a sudden bout of phobia that dominates the thinking of the individual as these activate Thoughts when remembering a situation, an accident or a painful experience, which doubles the heartbeat and increases the level of adrenaline in the blood, as the bad thoughts and frustrated feelings strengthen each other, which leads the individual to lose these disturbing thoughts associated with stress and thus panic appears in the form of attacks of sudden physical signs and loss Awareness, however, that there are some treatments that limit these diseases, especially the technique that was reached by chance by a doctor with an incurable disease, which is a method of desensitization to rapid eye movement, as this method is considered one of the effective methods in treating trauma and negative thoughts, as the spread of This technique is widely used and has shown a strong effect with good results for people with mental illness